Penguatan Manajemen Pembelajaran Mendalam melalui Pemanfaatan Kecerdasan Artifisial Intelegensi bagi Guru Sekolah Dasar - Nurhidayati, Nurhidayati; Arum Ratnaningsih; Ferdian Ferdian; Iin Cahyani; Elsa Agustina (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity aims to strengthen teachers' capacity to manage deep learning through the utilization of artificial intelligence (AI) in elementary school classrooms. The rapid development of AI technology provides opportunities for teachers to design more personalized learning, conduct assessments efficiently, and make data-driven learning decisions. The program is implemented in three stages: preparation, execution, and evaluation. The preparation stage includes the development of training modules and mapping relevant AI applications to support deep learning. The execution stage consists of workshops, hands-on practice using AI applications, and collaborative development of teaching materials by teachers. Evaluation is conducted through reflective assessments, task performance evaluations, and follow-up interviews. The results of the activity show significant improvements in teachers' understanding of AI-based deep learning management, including the ability to use AI for lesson planning, formative assessment, and analyzing students' learning progress. Teachers also reported increased confidence in integrating AI into teaching activities and recognized the benefits of AI in promoting students' higher-order thinking skills. This program demonstrates that strengthening teachers' competencies in utilizing AI can enhance the quality of deep learning management in elementary schools.